2008
DOI: 10.1007/s00330-008-1194-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined FDG-PET/CT for the detection of unknown primary tumors: systematic review and meta-analysis

Abstract: The aim of this study was to systematically review and meta-analyze published data on the diagnostic performance of combined 18F-fluoro-2-deoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) in the detection of primary tumors in patients with cancer of unknown primary (CUP). A systematic search for relevant studies was performed of the PubMed/MEDLINE and Embase databases. Methodological quality of the included studies was assessed. Reported detection rates, sensitivities and specificities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
223
5
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(249 citation statements)
references
References 47 publications
(106 reference statements)
7
223
5
9
Order By: Relevance
“…CT scan and MRI are useful, especially in the detection of primary breast tumors. A recent meta-analysis :http://dx.doi.org/10.7314/APJCP.2014.15.1.363 CEA, AFP, CA125, CA153 and CA199 in Malignant Pleural Effusions Predict the Cause (Kwee et al, 2009) showed that, overall, FDG-PET/CT was able to detect 37% of primary tumors in patients with CUP, with both sensitivity and specificity of 84%. On the other hand, it should be realized that FDG-PET/CT is an expensive examination, and false-positive FDG-PET/CT findings may result in unnecessary additional invasive diagnostic procedures, which have associated morbidities and costs (Kwee et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…CT scan and MRI are useful, especially in the detection of primary breast tumors. A recent meta-analysis :http://dx.doi.org/10.7314/APJCP.2014.15.1.363 CEA, AFP, CA125, CA153 and CA199 in Malignant Pleural Effusions Predict the Cause (Kwee et al, 2009) showed that, overall, FDG-PET/CT was able to detect 37% of primary tumors in patients with CUP, with both sensitivity and specificity of 84%. On the other hand, it should be realized that FDG-PET/CT is an expensive examination, and false-positive FDG-PET/CT findings may result in unnecessary additional invasive diagnostic procedures, which have associated morbidities and costs (Kwee et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the exact causes of false positive FDG-PET/CT/CT results is scarce, although benign inflammatory lesions and pulmonary infarction have been reported aetiologies [9]. The oropharynx and the lung are the two most common locations of false-positive FDG-PET/CT/CT results [10].…”
Section: Discussionmentioning
confidence: 99%
“…and A.K.H.M.) independently assessed the quality of the included studies using the quality assessment of diagnostic accuracy studies criteria modified by Kwee and Kwee [10]. Twelve methodological quality items were assessed for each study using the scores "yes," "no," or "unclear" for each item.…”
Section: Study Quality Assessmentmentioning
confidence: 99%